Cross regulation in flyback converters analytic model and solution. - Chuanwen Ji (IEEE Transactions on power electronics)
An analytical model for studying cross regulation among the multiple outputs of flyback converters is presented in this paper. Both the theoretical and experimental results show that the cross regulation can be improved by lowering the clamp voltage, which has not been previously reported. Many other factors, such as the leakage inductance in primary and secondary windings, the magnetizing inductance, and the air gap can also affect the cross regulation. Detailed analysis and test results are provided. Based on this model, a cost-effective passive energy regenerative clamp is proposed that allows the clamp voltage to be much lower than that of traditional RC clamps, thus improving the cross regulation and energy efficiency